Performance metrics in air traffic management systems - Hulda Ástþórsdóttir 1964- (2013)
Over several years there has been increasing demand world-wide for more capacity in Air Traffic Management Systems as air traffic has continued to grow. At the same time there is growing demand for quality of the service provided by the Air Navigation Service Providers as well as for lower charges. This has led to efforts by the European Union, through a major initiative called the Single European Sky, to increase the efficiency of Air Traffic Management in Europe. As a result of this development, much emphasis has been put on efforts to control cost and use financial resources in a more efficient way. An important development for this purpose has been the introduction of formal metrics for assessing service provider performance. The airspace controlled by Iceland, the Reykjavík Control Area, spans approximately 5.4 million square kilometres and is mainly oceanic apart from the area over northern Greenland. Isavia is the Air Navigation Service Provider responsible for providing air navigation services in this area. This study is directed at the en-route Air Navigation Service provided in this area. The aims of this thesis are to analyse and evaluate the metrics that are currently used to measure the performance of Air Navigation Service Providers and to develop a system of performance metrics for the Icelandic Air Traffic Management System. In this thesis, performance metrics which have been used in benchmarking Air Navigation Service Providers were studied as well as the factors affecting performance. Several performance metrics are calculated using data from Isavia. The results of the calculations are compared to other oceanic Air Navigation Service Providers. The productivity was also compared to the Maastricht Upper Area Control Centre since this centre provides only en-route Air Navigation Services similar to the oceanic en-route services provided by Isavia. Isavia offers user-preferred tracks in most of its control area. Also radar surveillance is available in a large part of the area. This affords more ...